BETWEEN THE PACIFIC COAST, THE MOUNTAIN AND THE PLAIN, COLOMBIA HAS ALSO SOUTH - Carreno Tarazona, Clara Ines [UNESP] (Asoc Historia Abierta, 2016)
This article analyzes the resulting geographic, socioeconomic and political environment from the predominance of an extensive network of roads that articulated the territory between the Pacific Coast to the Plains of southern Colombia during the first decade of the of the 20th century. First, it deals the activities and customs of the space corresponding to the lower region of Narino. Secondly, it examines the Region Mountain and moor as a point of confluence of the exchanges between the lowlands and the Plain. Finally, it examines the relationship between the discourse on the recognition of the territory and diplomatic reasons for the protection of the borders. Sources edit employees are the notes of travel in the South of Colombia of the engineer Miguel Triana and geographer engineer Francisco Javier Vergara y Velasco, delegates of the Government of Rafael Reyes for the exploration and graphical representation of the territory, respectively.
Keywords: Roads; territory; Pacific coast; mountains; Plain; diplomacy